Determination of Education, Poverty, and GDP per Capita on Economic Growth in Indonesia - Hamid, Ahmad Musleh Abdul (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2025)
This study aims to analyze the effect of education, poverty, and GDP per capita on economic growth in Indonesia through a panel data regression analysis approach in seven provinces during the period 2017-2022 using the Eviews tool. The results show that poverty has a significant negative impact on economic growth, where high poverty rates hinder productivity and economic development. In contrast, education has a significant positive effect on economic growth, reinforcing the importance of investing in improving the quality of human resources to support innovation and competitiveness. In addition, GDP per capita also has a significant positive relationship with economic growth, reflecting the role of people's productive capacity and purchasing power in driving economic activity. This study confirms the importance of integrated policies, including poverty reduction, improving the quality of education, and optimizing the management of economic resources to achieve inclusive and sustainable economic growth.